STRATEGI PENYUSUNAN INSTRUMEN EVALUASI UNTUK MENGUKUR KEMAMPUAN BERPIKIR TINGKAT TINGGI (HIGHER ORDER THINKING SKILLS) - Hesti Novita Sari; Ernawati; Musalamatul Husna; Rizki Wirayuda (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to describe the strategies for developing assessment instruments used to measure higher-order thinking skills (HOTS), their implementation in the classroom, and the challenges and efforts to improve the quality of these instruments. The scope of the study focuses on the process of developing HOTS assessment instruments, ranging from the analysis of learning outcomes (CP) and learning objectives (TP), the formulation of indicators, the development of a test blueprint, the creation of stimuli, the writing of test items, the development of a scoring rubric, validation, to the pilot testing of the instruments based on various relevant research findings. This study employs a library research method with a descriptive qualitative approach. The research data consists of secondary data obtained from scientific articles, books, conferrence proceedings, and academic documents published within the last ten years, which were then analyzed using content analysis techniques through data reduction, classification, presentation, interpretation, and drawing of conclusions. The results of the study indicate that the development of HOTS instruments must be carried out systematically, taking into account learning competencies, cognitive levels C4–C6, contextual stimuli, scoring rubrics, expert validation, and empirical testing, in order to produce instruments that are valid, reliable, and objective. The implementation of HOTS instruments can measure students’ abilities to analyze, evaluate, and create solutions more accurately. However, their development still faces challenges, particularly regarding teacher competence and the quality of instrument design. Therefore, training, mentoring, ongoing validation, and the use of digital technology are needed to improve the quality of HOTS assessment instruments.